Comparison of new scoring method, DEER scoring, in comparison to different endometrial pathology. - Koteshwara, Sowmya; Ramachandra, Vyshali; Bhat, Vibha; Ajjammanavar, Virupaksha (Journal of Neonatal Surgery, 2025)
Background: Abnormal uterine bleeding (AUB) is not an uncommon occurrence and accounts for about 10-30% of chief complaints reported by women, with >30% of them occurring during the premenopausal phase & >70% of visits amongst peri and postmenopausal phase. Therefore, in order to overcome the shortcomings of the current diagnostic modalities, it is important to use a simple assessment cum diagnostic tool such as DEERS which can be implemented to screen women presenting with AUB. Aims: To validate a non-invasive screening tool such as Disease of Endometrium Evaluation and Risk Scoring (DEERS) in woman with abnormal uterine bleeding in comparison to endometrial biopsy Materials & Methods: A cross-sectional case control hospital based study was carried out amongst abnormal uterine bleeding patients attending Department of Obstetrics & Gynecology, JSS Hospital, Mysuru with 158 cases and 158 controls. Histopathological evaluation & DEERS scoring system was carried out to understand the efficacy of the new scoring system. Quantitative data was summarized using Mean (SD) with Student t-test, ANOVA used to test the significance with P value as <0.05 for statistical significance. Results: Amongst cases 44.67% subjects were aged 51-60 years; however, amongst controls, majority of subjects (78.67%) who were aged ≤50 years. Histopathological evaluation revealed 45 endometrial hyperplasia without atypia, 27 disordered proliferation, 18 endometrial polyp, 6 endometrial malignancy and 9 endometrial hyperplasia with atypia cases with DEERS score showing 4 (2.67%) normal endometrium, 123 (82.0%) benign pathologies, 12 (8.0%) complex hyperplasia and 11 (7.33%) endometrial malignancies with mean scores of 8.0, 12.12, 19.5 and 26.91 respectively. In benign pathologies, we found sensitivity, specificity, PPV & NPV of 94.55%, 52.50%, 84.55% and 77.78% respectively, whereas it was 27.27%, 94.24%, 27.27% and 94.24% in malignant cases. Conclusion: The new scoring diagnostic method was found to be effective in determining the type of lesions seen in abnormal uterine bleeding and in the current scenario when there is a lack of studies with respect to this system; we advocate it to be used as an adjunctive diagnostic modality. Also, we recommend more studies in this regard with a consideration for more factors to understand the role of other confounding factors which may determine the exact diagnosis.